ENGLISH PROFICIENCY AND MOTIVATION AMONG MALE AND FEMALE UNDERGRADUATE ESL LEARNERS IN TURBAT, BALOCHISTAN (Contemporary Journal of Social Science Review, 2026)
The current study explored the motivation of the undergraduate learners to learn English in Turbat, Balochistan. It investigated the impact of proficiency on the motivation of the learners and also examined gender differences in English learning motivation and proficiency among undergraduate students. The data for the current study was collected from undergraduate students of Turbat, Balochistan in University of Turbat and two degree colleges of the city. The data collection was done through five-point Likert scale questionnaire and it was followed by a proficiency test and semi-structured interviews. The quantitative data was analyzed through simple regression analysis using SPSS. The results revealed that proficiency was a significant predictor of learners’ motivation to learn English in Turbat, Balochistan. The results also showed that both of the genders had a good proficiency in English as their scores in last exam in English were good and they performed well in proficiency test as well. Furthermore, the study found noticeable gender differences among the participants. Female students performed comparatively better than male students in both previous English examination scores and the proficiency test, which may suggest comparatively stronger motivation and engagement toward learning English among female learners.